Управление характеристиками фильтрующих компонент первого порядка в специализированных компьютерных системах - Дикусар, Е. В. (Видавництво Львівської політехніки, 2011)
In work is considered the operate of components at the expense of change of their frequency characteristics.
Keywords: amplitude-frequency and phase-frequency characteristic; indicator of pulsations; cut-off frequency